Metode Penulisan Sejarah al-Thabari Kasus Peristiwa Fath Makkah - Saidun Derani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
Mecca occupation (Fath Makkah) on 8 H/ January 630 M was a phenomenal and historical moment in islamic history. many muslim historians studied this event such as al-Thabari through his masterpiece, Tarikh al-Umam wa al-Muluk or Tarikh al-Rasul wa al-Muluk. Al-Thabari analysed this event by applying the